Gear‐Switch‐Integrated Dual‐Mode Three‐Wheeled Exoskeleton that Empowers Cyborg Insects with Enhanced Open‐Loop Locomotion Control Precision and Load Capacity - Rui Li; Zezhong Zhang; Duc Long Le; Chen Lv; Sun Woh Lye; Hirotaka Sato (Advanced Intelligent Systems)
Cyborg insects are potential alternatives to small artificial robots, with promising applications in areas such as confined space exploration. However, its low open‐loop locomotion control precision makes it difficult to perform tasks requiring precise control, while the number of sensors that can be carried is limited due to their low load capacity, which significantly limits its application scenarios. To this end, an exoskeleton is proposed herein, which significantly improves the locomotion control accuracy and load capacity of cyborg insects. The exoskeleton, with a peripheral size of 7.2 cm × 14 cm, employs three wheels to carry the load and control the direction of motion of the cyborg insect. The exoskeleton‐integrated cyborg insect excels in locomotion control precision. Without feedback control, it completes continuous circular and linear motions with minor offset errors. Compared to other cyborg insects, its load capacity is increased from less than 20–400 g or more, allowing it to be equipped with large, energy‐intensive sensors. In addition, the exoskeleton supports switching between high‐precision controlled motion and insect‐driven active exploration modes. This design broadens the application scenarios of the cyborg insect and opens the possibility of performing more complex tasks.